Missed Opportunities for Screening and Management of Dysglycemia among Patients Presenting with Acute Myocardial Infarction in North India: The Prospective NORIN STEMI Registry - John W. Ostrominski; Muthiah Vaduganathan; Meennahalli Palleda Girish; Puneet Gupta; Michael J. Hendrickson; Arman Qamar; Sameer Arora; Ambarish Pandey; Ankit Bansal; Vishal Batra; Bhawna Mahajan; Saibal Mukhopadhyay; et al. (Ubiquity Press, 2022)
Background: Dysglycemia is a major and increasingly prevalent cardiometabolic risk factor worldwide, but is often undiagnosed even in high-risk patients. We evaluated the impact of protocolized screening for dysglycemia on the prevalence of prediabetes and diabetes among patients presenting with ST-segment elevation myocardial infarction (STEMI) in North India. Methods: We conducted a prospective NORIN STEMI registry-based study of patients presenting with STEMI to two government-funded tertiary care medical centers in New Delhi, India, from January to November 2019. Hemoglobin A1c (HbA1c) was collected at presentation as part of the study protocol, irrespective of baseline glycemic status. Results: Among 3,523 participants (median age 55 years), 855 (24%) had known diabetes. In this group, baseline treatment with statins, sodium-glucose cotransporter 2 inhibitors, or glucagon-like peptide-1 receptor agonists was observed in 14%, <1%, and 1% of patients, respectively. For patients without known diabetes, protocolized inpatient screening identified 737 (28%) to have prediabetes (HbA1c 5.7-6.4%) and 339 (13%) to have newly detected diabetes (HbA1c ≥ 6.5%). Patients with prediabetes (49%), newly detected diabetes (53%), and established diabetes (48%) experienced higher rates of post-MI LV dysfunction as compared to euglycemic patients (42%). In-hospital mortality (5.6% for prediabetes, 5.1% for newly detected diabetes, 10.3% for established diabetes, 4.3% for euglycemia) and 30-day mortality (8.1%, 7.6%, 14.4%, 6.6%) were higher in patients with dysglycemia. Compared with euglycemia, prediabetes (adjusted odds ratio (aOR) 1.44 [1.12-1.85]), newly detected diabetes (aOR 1.57 [1.13-2.18]), and established diabetes (aOR 1.51 [1.19-1.94]) were independently associated with higher odds of composite 30-day all-cause mortality or readmission. Conclusions: Among patients presenting with STEMI in North India, protocolized HbA1c screening doubled the proportion of patients with known dysglycemia. Dysglycemia was associated with worse clinical outcomes at 30 days, and use of established pharmacotherapeutic risk-reduction strategies among patients with known diabetes was rare, highlighting missed opportunities for screening and management of dysglycemia among high-risk patients in North India.